Hermeneutika Modern: Sebuah Pengenalan Awal (I) - Kusmana Kusmana (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2005)
The development of knowledge is a dialectic of social dynamics and knowledge itself, including theology. From there, various forms of knowledge emerged, eventually crystallizing into disciplines. One of them is hermeneutics, a field that can be simply understood as the science of interpretation. Initially, this science served as a prerequisite for deciphering religious texts that were considered final and sacred. That's why hermeneutics as a discipline is closely related to the world of theology, specifically the sub-discipline of theology that deals with methodology and authentication in the interpretation of Scripture in both the Christian and Jewish traditions. This article describes modern hermeneutics from the aspects of understanding, history, and its divisions into methodological, philosophical, and critical hermeneutics.